Protection, maintenance & development of awqaf in India (with special reference to Rajasthan) - Rashid, Syed Khalid (Institute of Objective Studies, 2005)
Awqaf resources constitute a major component of the social wealth of the Muslims. As the institution of waqf belongs to the non-governmental sector, it is but logical that it shall be managed not by the government but by the Muslims, particularly in the institution of Qadi in India that was abolished in 1864 by the British.